The anti-inflammatory mechanism of acerola based on LPS-induced RAW264.7 macrophages and xylene-induced ear edema in mouse - Hua Wu; Liuping Fan; Qun Yu; Yanqing Li; Ling Tong; Cuifeng Cao (Journal of Functional Foods)
Acerola cherry has been acknowledged as the best source of natural vitamin C supplements, while the anti-inflammatory effect of acerola (ACC) is still unclear. Component analysis showed that the contents of vitamin C and flavonoids reached 18 % and 2.98 %, respectively. To explore the potential mechanism of ACC on LPS-induced RAW264.7 inflammation, the expression of proinflammatory cytokines and protein were assessed. ACC inhibited the activation of the iNOS, NF-κB, JAK-STAT3 and MAPK pathways, thus reducing the levels of NO, TNF-α, IL-1β and IL-6. Additionally, ACC exhibited better anti-inflammatory activity than Vc alone. Vc and flavonoids in ACC inhibited xylene-induced ear edema via hindering the generation of TNF-α, IL-1β and inflammatory mediator PGE2. Middle and high doses of Vc and flavonoids were beneficial to alleviate ear inflammation in mice. Significantly, the ear weight and thickness variation were only 16.16 % and 14.91 % under ACC administration, which were the lowest.